Oxidation catalyst degradation in the exhaust stream of a large bore 2-stroke natural gas engine - Davis, Kristen, author; Olsen, Daniel, advisor; Holland, Troy, committee member; De Miranda, Michael A., committee member (Colorado State University. Libraries, 2015)
Lean burn 2-stroke natural gas engines are commonly used for power generation and gas compression. These engines, however, contribute to air pollution primarily through emissions of carbon monoxide, volatile organic compounds and some unburned hydrocarbons. Oxidation catalysts aid in reducing these harmful emissions. Lubrication oil carryover to engine exhaust degrades the oxidation catalyst making it less effective at reducing emissions. This work combines laboratory and field testing of an oxidative catalyst designed for lean burn natural gas engines. Catalyst performance is tracked over the course of a year to examine the rate and cause of degradation. The oxidation catalyst was housed in a slipstream in the exhaust stream of a Copper-Bessemer GMVH12 large bore 2-stroke natural gas engine between one and two months at a time. The catalyst was periodically removed and returned to the laboratory for emissions and material testing. Emissions testing was completed by diverting exhaust gas from a Cummins QSK19 4-stroke stationary natural gas engine through a slipstream. A fourier transform infra-red spectrometer and a 5-Gas analyzer were used to determine the exhaust composition pre-catalyst and post-catalyst. Lubrication oil carry over and poisoning decreases the oxidation catalysts ability to reduce emissions, materials testing was performed to determine the exact levels of the poisons, such as sulfur, phosphorous and zinc. A scanning electron microscope and X-Ray spectrometer were used to complete materials testing. The catalyst material initially showed a sharp increase in sulfur poisoning, but it quickly leveled off around 3 atomic%. Phosphorous and zinc poison buildup, however, rose throughout the duration of this study. As the catalyst experienced increasing levels of poison buildup, the reduction efficiency of emissions decreased due to blocked active catalyst sites. Laboratory emissions testing showed degradation of reduction efficiency for carbon monoxide, formaldehyde and volatile organic compounds. During each round of testing, a temperature sweep and a space velocity sweep were completed. The temperature sweeps were run between 300°F (149°C) and 800°F (827°C) at 150,000 hr⁻¹ and the space velocity sweeps were run between approximately 20,000 hr⁻¹ to 200,000 hr⁻¹ at 550°F (287°C). Reduction efficiencies for carbon monoxide, formaldehyde, propylene, ethylene and volatile organic compounds decreased over the six tests. Carbon monoxide reduction efficiency remained high, above 90%, throughout all temperature sweep tests. Formaldehyde exhibited high reduction efficiency, over 70%, for all tests, and its reduction efficiency decreased by 19% at 450°F and 4% at 600°F during the temperature sweep tests. Propylene showed the highest level of degradation. Over six tests, the reduction efficiency for propylene dropped 36% at 450°F and 28% at 600°F during temperature sweeps. Like carbon monoxide, ethylene maintained a reduction efficiency above 90% for all tests during the temperature sweeps. Volatile organic compound reduction efficiency, on the other hand, did not exceed 80% for any temperature sweep tests. Methane, propane and ethane reduction efficiencies were low and erratic for both temperature and space velocity sweeps for all tests.
Keywords: large bore 2-stroke; oxidation catalyst; natural gas; degradation